Ensaios clínicos da iniciativa do investigador e descrição do estágio em coordenação de estudos clínicos no IPO Porto - Bastos, Inês Maria Capelo (2022)
This report aims to describe the activities performed during the internship in Clinical Trials Coordination at the Clinical Research Unit of IPO Porto, as well as to provide an overview of the state-of-the-art of investigator-initiated trials. The internship took place between September 20, 2021 and January 31, 2022, and its main objective was the practical application of theoretically covered concepts and the direct and daily contact with the coordination of clinical trials in the oncologic area. During the internship, and with the contact with different types of trials, it was concluded that it would be relevant to approach trials at the investigator's initiative. Thus, this report is organized into two parts, the first consisting of a literature review on investigator-initiated trials, and the second consisting of the description of the activities performed during the internship. During this internship, it was possible to collaborate with the different clinics that make up the Clinical Research Unit, which was extremely important for the enrichment of the internship experience. Daily coordination activities were performed, such as filling out eCRFs, screening and randomizing participants, and preparing scripts for protocol visits, among others. The contact with 38 clinical trials and 1 observational study during the internship period allowed for the consolidation of previously obtained knowledge and contact with the daily reality of clinical trial coordination. In addition, the literature review on investigator-initiated trials was also very relevant to understand the state of the art globally and the main changes needed to combat the barriers that still exist to conducting this type of trial.